Metal and Metal Oxide Nanoparticles: Design, Characterization, and Biomedical Applications - Limongi, Tania (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Developing new materials is usually a time-demanding and meticulous process, but at the same time, it is one of the more promising solutions to obtain a cleaner, safer, and smart future. More in detail, referring to nanomaterials, an increasingly successfully tool of nanotechnologies, nanoparticles are categorized as materials in which at least one dimension is less than 100 nm in diameter. Among the various nanoparticles' categories, metal and metal oxides nanoparticles stand as an emerging nanotechnological solution for a wide range of biological and medical physio/pathological open questions. This Special Issue covers the fundamental science, design, characterization, and biomedical applications of metal and metal oxide nanomaterials. The articles here presented will embrace all the aspects determining the performance of these systems, ranging from their synthesis, design, chemical, physical, and biological functionalization, to their characterization and successful applications.